LIPASE PRODUCTION FROM Aspergillus niger BY SOLID STATE FERMENTATION AND ITS APPLICATIONS - SUMATHY R; VIJAYALAKSHMI.M (International Journal of Pharma and Bio Sciences, 2014)
This study reviews the application of Solid State Fermentation (SSF) to the production of lipase enzyme. Lipase production has been investigated by SSF of agro-industrial wastes like coconut oil cake, wheat rava, wheat bran, gingelly oil cake etc., by Aspergillus niger MTCC 2594. Highest enzyme production was obtained by combination of wheat bran, coconut oil cake, wheat rava (5:2:1), with moisture content of 1:1.5, 250ml of spore suspension at 30oC. Media supplementation with nitrogen source as commercial casein (0.5%) and Palm oil increased enzyme production, to 559U/g DS (Dry substrate) and with a productivity rate of 7.76 Units per hour. Initial studies on enzymatic hydrolysis of different vegetable oils by lipase produced by SSF showed that palm oil was hydrolyzed efficiently to 74.49% after 72 hours of reaction time and with 50U of lipase.